Penguatan Kapasitas Kelembagaan dalam Pembangunan Kelurahan Berkelanjutan Berbasis Agrowisata di Kumpulrejo, Kota Salatiga - Rahayu Rafikahwulan Sari; Royke Robert Siahainenia; Suryo Sakti Hadiwijoyo (Jurnal Wilayah dan Lingkungan, 2020)
Kumpulrejo Village becomes the priority of Salatiga City in the sustainable village development based on the local potential of agrotourism. Kumpulrejo holds potential in livestock farming, nearly 80% of the population are dairy farmers. Suboptimal institutional capacity of the Livestock Farmer Groups in managing potentials results in problems regarding sustainable village development program in Kumpulrejo. The community’s social capital is expected to significantly affect the Livestock Farmer Groups’s institutional capacity strengthening. The present study aims to find out the affect of social capital on the institutional capacity strengthening with regard to argoturism-based sustainable village development in Kumpulrejo. The method that used was quantitative-descriptive, data obtained from questionnaires, observation, and interview. The sampling technique used by simple random sampling, to the 60 respondents. The study showed that social capital which consist of a trust, social network, and norms significantly affect to the institutional capacity strengthening by 57,9%. Partially, a trust did not hold significantly affect, while social network and norms significantly affect the institutional capacity strengthening of livestock farmer groups in Kumpulrejo Village.